2000
DOI: 10.1159/000016066
|View full text |Cite
|
Sign up to set email alerts
|

Management of Resistant Hypertension in Patients with Carotid Stenosis: High Prevalence of Renovascular Hypertension

Abstract: Introduction: Patients with carotid stenosis are at high risk of vascular events and therefore require an optimal control of risk factors such as hypertension. As the treatment of hypertension differs according to the cause, we examined the prevalence of resistant hypertension, and the cause of hypertension, among patients with carotid stenosis followed closely in two randomized trials of carotid endarterectomy. Objective: The purpose of this study was to determine the prevalence of resistant hypertension and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Higher prevalence of subclinical organ damage can be found in patients with resistant hypertension, including left ventricular hypertrophy [18], intima-media thickening and carotid atheroma [19], hypertensive retinopathy, albuminuria and initial impairment of renal function [20,21].…”
Section: Prognosismentioning
confidence: 99%
“…Higher prevalence of subclinical organ damage can be found in patients with resistant hypertension, including left ventricular hypertrophy [18], intima-media thickening and carotid atheroma [19], hypertensive retinopathy, albuminuria and initial impairment of renal function [20,21].…”
Section: Prognosismentioning
confidence: 99%
“…The mechanism has been called "kicking the back door out of the glomerulus" [23]. I have reported that among patients with carotid stenosis and resistant hypertension, 25% have renovascular hypertension [24]. Therefore, oral angiotensin-converting enzyme inhibitors or angiotensin II receptors are not safe in patients with stroke.…”
Section: Intravenous Sodium Nitroprussidementioning
confidence: 99%
“…However, it is likely that patients with large-artery atherosclerosis will benefi t. Many physicians are, however, cautious about lowering blood pressure, particularly in patients with severe bilateral carotid stenosis or occlusion. These patients often also have disease of the vertebral arteries, the carotid siphon, and the cerebral arteries (Thiele et al 1980;Gorelick 1993) and have a particularly high risk of recurrent stroke (Spence 2000). Loss of the normal autoregulatory capacity of the cerebral circulation, such that cerebral blood fl ow is directly dependent on systemic blood pressure, is common (Van der Grond et al 1995;Grubb et al 1998), and there has been natural concern that blood pressure lowering may reduce cerebral perfusion and increase the risk of stroke.…”
Section: Blood Pressure Lowering -Most Patientsmentioning
confidence: 99%